Dendritic Polymers in Tissue Engineering: Contributions of PAMAM, PPI PEG and PEI to Injury Restoration and Bioactive Scaffold Evolution - Michael Arkas; Michail Vardavoulias; Georgia Kythreoti; Dimitrios A. Giannakoudakis (MDPI AG, 2023)
The capability of radially polymerized bio-dendrimers and hyperbranched polymers for medical applications is well established. Perhaps the most important implementations are those that involve interactions with the regenerative mechanisms of cells. In general, they are non-toxic or exhibit very low toxicity. Thus, they allow unhindered and, in many cases, faster cell proliferation, a property that renders them ideal materials for tissue engineering scaffolds. Their resemblance to proteins permits the synthesis of derivatives that mimic collagen and elastin or are capable of biomimetic hydroxy apatite production. Due to their distinctive architecture (core, internal branches, terminal groups), dendritic polymers may play many roles. The internal cavities may host cell differentiation genes and antimicrobial protection drugs. Suitable terminal groups may modify the surface chemistry of cells and modulate the external membrane charge promoting cell adhesion and tissue assembly. They may also induce polymer cross-linking for healing implementation in the eyes, skin, and internal organ wounds. The review highlights all the different categories of hard and soft tissues that may be remediated with their contribution. The reader will also be exposed to the incorporation of methods for establishment of biomaterials, functionalization strategies, and the synthetic paths for organizing assemblies from biocompatible building blocks and natural metabolites.